Chronic Patients' Autonomy in Iranian Hospitals: A Qualitative Study. Issue 1 (2nd January 2017) - Ebrahimi, Hossein; Sadeghian, Efat; Seyedfatemi, Naeimeh; Mohammadi, Eesa
Abstract : The autonomy of chronic patients in Iranian hospitals is challenged by impaired functioning resulting from chronic illness, a negative image in society, and effects related to hospitalization. Comprehensive interviews and observations of 34 patients, nurses, and physicians were performed to assess the autonomy of chronic patients in Iran. Conceptualization, constant comparison, and the combination of data resulted in the identification of 5 main categories related to autonomy: welcoming paternalism, self-expression, self-proof, shared decision making, and self-determination. Authority scrambling was a central category describing chronic patients' perceptions of their autonomy during hospitalization. These patients sought to maintain their independence despite serious threats to their autonomy.